2014
DOI: 10.1177/1088767914554616
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Context and Media Constructions of Murder

Abstract: Utilizing data from multiple local newspapers, this study examines disparities in the presence/absence and amount of newspaper coverage given to homicide victims in Los Angeles County, California. Multilevel logistic and negative binomial regressions indicate that the level of economic disadvantage and percentage of minority residents in/around the crime scene neighborhood negatively affects the presence/absence and rate of newspaper coverage. These findings contribute to the literature by highlighting the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 78 publications
(210 reference statements)
0
2
0
Order By: Relevance
“…There is a distinction in news coverage depending on the race of the criminal as well as the victim. Stories involving Black and Latino victims receive less news coverage than those involving White victims (Petersen, 2016;Sacco, 1995). Petersen (2016) found that even the neighborhood in which the crime occurred impacted the coverage the crime received.…”
Section: Crime Newsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a distinction in news coverage depending on the race of the criminal as well as the victim. Stories involving Black and Latino victims receive less news coverage than those involving White victims (Petersen, 2016;Sacco, 1995). Petersen (2016) found that even the neighborhood in which the crime occurred impacted the coverage the crime received.…”
Section: Crime Newsmentioning
confidence: 99%
“…Stories involving Black and Latino victims receive less news coverage than those involving White victims (Petersen, 2016;Sacco, 1995). Petersen (2016) found that even the neighborhood in which the crime occurred impacted the coverage the crime received. Homicides that occurred in or around disadvantaged areas were less likely to receive news coverage at all.…”
Section: Crime Newsmentioning
confidence: 99%